Natural language generation: The commercial state of the art in 2020. (July 2020) - Dale, Robert
Abstract: It took a while, but natural language generation is now an established commercial software category. It's commented upon frequently in both industry media and the mainstream press, and businesses are willing to pay hard cash to take advantage of the technology. We look at who's active in the space, the nature of the technology that's available today and where things might go in the future.